Justice Development Programming in Fragile and Conflict-Affected Areas : Perspectives of Two Leaders in Justice Administration - Azimi, Abdul Salam (World Bank, Washington, DC, 2014)
This spoken presentation profiles the efforts of the Supreme Court of Afghanistan to produce effective plans for developing that court and the judicial system in general. It offers an assessment of the limits of financial assistance by donors in bringing about rapid improvements in the quality of the judiciary. It argues for the need to invest in the human capital of the justice system as the most important though time consuming strategy for overcoming poor judicial performance and reducing corruption in the justice system. It also explains the strategic planning processes of the Supreme Court of Afghanistan and the reasons why the court's current plan deserves continued and sustained support from donors.